Changes in treatment landscape of relapsed or refractory multiple myeloma and their association with mortality: Insights from German claims database. (20th November 2020) - Scheid, Christof; Blau, Igor W.; Sellner, Leopold; Ratsch, Boris A.; Basic, Edin
Abstract: Objectives: Emerging treatments for relapsed or refractory multiple myeloma (rrMM) have led to increasing options for many patients. This study aimed to assess changes in utilization of these options in Germany with a focus on modern triplet regimens including new agents, such as carfilzomib, ixazomib, elotuzumab and daratumumab, and to evaluate whether this had an impact on rrMM‐related outcomes over time. Methods: The study population consisted of 1255 rrMM patients who were assigned to one of the following 6 treatment groups: immunomodulatory drug (IMiD)‐based doublets, proteasome inhibitor (PI)‐based doublets, daratumumab monotherapy, PI‐IMiD‐based triplets, monoclonal antibodies (mAbs)‐based triplets, or other treatment. Results: Use of triplet‐based therapy regimens increased from 5.9% in 2014 to 31.4% in 2017. In parallel, use of IMiD‐based doublets decreased from 74.3% in 2014 to 37.6% in 2017. Over the same time period, the risk of death decreased by 32% and the risk of hospitalization which was reduced by 30%. The risk for serious adverse events remained unchanged. Conclusions: Between 2014 and 2017, the use of triplet‐based therapy regimens for rrMM in Germany has significantly increased and this was associated with a significant decline in deaths and hospitalizations without an increased incidence of serious adverse events.